Russian and Soviet Sociolinguistics and Taboo Varieties of the Russian Language (Argot, Jargon, Slang and "Mat") Transl. into Engl. by Nortrud Gupta. Rev. and Enlarged ed - von Timroth, Wilhelm (Slavistische Beitraege, 1986)
This thesis presents a survey of the research done on social varieties which have been taboo in the Soviet Union for some decades. It includes the research done before and after the October Revolution. It also traces the influence of politics on sociolectology and reviews in this connection the work of a Bulgarian linguist on social dialects.